Alkaloids from the flower of Erythrina arborescens. Issue 81 (3rd November 2017) - Wu, Jing; Zhang, Bing-Jie; Xiao, Wen-Na; Bao, Mei-Fen; Cai, Xiang-Hai
Abstract : Phytochemical investigations on the flower of Erythrina arborescens resulted in the isolation of eight new Erythrina alkaloid, erytharborines A–H (1–8 ), together with 17 known alkaloids. Abstract : Phytochemical investigations on the flower of Erythrina arborescens resulted in the isolation of eight new Erythrina alkaloid, erytharborines A–H (1–8 ), together with 17 known alkaloids. Erytharborines A/B (1–2 ) and C (3 ) possessed an 2 H -imidazole ring and a unique oxime moiety, respectively. The structures were elucidated on the basis of UV, IR, mass spectrometry and NMR spectroscopic data.